2017
DOI: 10.1186/s12889-016-3911-2
|View full text |Cite
|
Sign up to set email alerts
|

Body weight status of school adolescents in Terengganu, Malaysia: a population baseline study

Abstract: BackgroundBody weight is highly associated with overall health status. Being severely thin or obese may impose the risk of many health problems. Early detection of body mass index (BMI) status may help to reduce the associated comorbidities. Although many studies in the literature have investigated the BMI of school adolescents in Malaysia, the data on status of body weight among school adolescents in suburban states like Terengganu is limited. This study aimed to describe the body weight status of the whole p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…No research has studied the effects of online grocery shopping on the diets of SNAP participants, but several recent studies provide insight on the availability and uptake of online SNAP purchases [ 172 , 173 , 174 , 175 ]. Three studies have shown that, while online grocery can address transportation barriers and food availability, perceptions related to higher food costs online, lack of control over food quality, and distrust of the online shopping process may prevent SNAP participants from utilizing these services [ 173 , 174 , 175 ]. One attempted trial was unable to recruit enough SNAP participants to make online grocery purchases, mainly due to participants’ perceived lack of control over the quality of food selected [ 174 ].…”
Section: Resultsmentioning
confidence: 99%
“…No research has studied the effects of online grocery shopping on the diets of SNAP participants, but several recent studies provide insight on the availability and uptake of online SNAP purchases [ 172 , 173 , 174 , 175 ]. Three studies have shown that, while online grocery can address transportation barriers and food availability, perceptions related to higher food costs online, lack of control over food quality, and distrust of the online shopping process may prevent SNAP participants from utilizing these services [ 173 , 174 , 175 ]. One attempted trial was unable to recruit enough SNAP participants to make online grocery purchases, mainly due to participants’ perceived lack of control over the quality of food selected [ 174 ].…”
Section: Resultsmentioning
confidence: 99%
“…19 No significant relationship was found between obesity and the three main ethnicities in Malaysia, consistent with other study findings of body weight status in another state of the east coast region of Malaysia. 20 Malays had the highest prevalence of obesity, followed by the Indians and Chinese. In contrast with another study, Indian children had the lowest prevalence of overweight and obesity compared with the Malaysians and Chinese.…”
Section: Discussionmentioning
confidence: 96%
“…Each child will be asked to wear light clothing and no shoes during the measurements. Body weight and height will be measured to the nearest 0.1 kg and 0.1 cm, respectively [ 51 ], using an electronic SECA portable digital weighing scale (SECA 803, Hamburg, Germany) with an attached SECA stadiometer (SECA 217, Hamburg, Germany). All the measurements will be taken twice.…”
Section: Methodsmentioning
confidence: 99%